HPV prevention is not just for girls: an examination of college-age-students' adoption of HPV vaccines. Issue 3 (2nd July 2020) - Grantham, Susan; Connolly-Ahern, Colleen; Ahern, Lee
Abstract: This study identifies source(s) of information young adults found to be persuasive in choosing/declining HPV vaccines. The results indicate that males are not getting HPV vaccination information from either their physician, parent, or DTC advertising. Females reported that physicians and their mothers were the most influential sources of information. Additionally, females found that risk message frames focusing on empowerment, reduced dread, control and benefit in the DTC HPV vaccine advertisements were persuasive; males did not. With the rapid rise of HPV related cancers found in males, there is a need to inform males and their parents about for HPV vaccines.